The Influence of Job Satisfaction on Job Performance is Mediated by Organizational Commitment - Sari, Ajeng Purnama; Sojanah, Janah (Entrepreneurship Faculty, Universitas Garut, 2023)
Abstract– Human resources are one of the important factors in an organization or company, in addition to other factors such as assets and capital. Every organization and company will always try to improve the performance of its employees to achieve company goals. Performance is often a problem that arises among employees. The design used in this research is a cross sectional method. This type of research uses a verification method with an explanatory survey. The sampling technique used is a probability sampling technique using sampling of 100 respondents by distributing questionnaires. The data analysis technique used is Partial Least Squares (PLS) with the computer software tool SmartPLS version 4.0. Based on the research results, it can be seen that there is an influence of job satisfaction on employee performance mediated by organizational commitment.